2015
DOI: 10.1016/j.jviromet.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

An insulated isothermal PCR method on a field-deployable device for rapid and sensitive detection of canine parvovirus type 2 at points of need

Abstract: Canine parvovirus type 2 (CPV-2), including subtypes 2a, 2b and 2c, causes an acute enteric disease in both domestic and wild animals. Rapid and sensitive diagnosis aids effective disease management at points of need (PON). A commercially available, field-deployable and user-friendly system, designed with insulated isothermal PCR (iiPCR) technology, displays excellent sensitivity and specificity for nucleic acid detection. An iiPCR method was developed for on-site detection of all circulating CPV-2 strains. Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 18 publications
0
38
0
2
Order By: Relevance
“…CPV causes acute hemorrhagic enteritis and myocarditis in dogs [5], and the mortality rate of the disease is high (up to 70%) in puppies [11,14]. The main method for controlling the disease in domestic animals is by vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CPV causes acute hemorrhagic enteritis and myocarditis in dogs [5], and the mortality rate of the disease is high (up to 70%) in puppies [11,14]. The main method for controlling the disease in domestic animals is by vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…Several assays have been reported for the detection or quantitation of CPV DNA [12][13][14][15][16][17][18], including PCR, nested PCR, iiPCR, RPA, LAMP-ELISA, LAMP-LFD, LAMP, polymerase spiral reaction, and SYBR Green based real-time PCR, but none of these assays enable differentiation CPV antigenic types and CPV-like viruses (MEV and FPV). Several other assays have been reported for the detection and differentiation of type 2-based vaccines and field strains of CPV [19] or typing of three antigenic types of CPV [20] or CPV and MEV [21] assay and MGB probe real-time RT-PCR, but none of these assays enables simultaneous detection and differentiation of four antigenic types of CPV.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the simplicity and efficiency of the RT- iiPCR coupled with the POCKIT nucleic acid analyzer (RT-iiPCR/ POCKIT) to rapidly amplify nucleic acids under isothermal conditions suggested that this assay could be a potential alternative for detection of DENV especially in remote field settings. This system has been shown to offer sensitivity, specificity, and clinical performance comparable to those of reference real-time PCR or nested PCR methods for various microbial pathogens in various clinical sample types (36)(37)(38)(39)(40)(41)(42)(43)(44)(45). One of the major advantages of RT-iiPCR is its simple protocol.…”
Section: Discussionmentioning
confidence: 99%
“…The downscaling in size of nucleic acid extraction and high‐speed real‐time PCR platforms is opening new opportunities for utility at or near the source of collection . In many cases, advancements in developing rapid, point‐of‐capture real‐time PCR platforms have been pioneered for veterinary applications, facilitating diagnosis and treatment in companion animal medicine as well as management and control of infectious disease affecting livestock production …”
Section: The Potential Of Rapid Point‐of‐capture (Poc) Diagnosticsmentioning
confidence: 99%